Is there any fraction crazier than this?

Algebra Level 3

Let a a , b b and c c be three distinct real constants. It is given that a 2 ( a b ) ( a c ) ( a + x ) + b 2 ( b c ) ( b a ) ( b + x ) + c 2 ( c a ) ( c b ) ( c + x ) p + q x + r x 2 ( a + x ) ( b + x ) ( c + x ) \frac { { a }^{ 2 } }{ \left( a-b \right) \left( a-c \right) \left( a+x \right) } +\frac { { b }^{ 2 } }{ \left( b-c \right) \left( b-a \right) \left( b+x \right) } +\frac { { c }^{ 2 } }{ \left( c-a \right) \left( c-b \right) \left( c+x \right) } \equiv \frac { p+qx+r{ x }^{ 2 } }{ \left( a+x \right) \left( b+x \right) \left( c+x \right) }

where p p , q q and r r are real constants. If s = 7 p + 8 q + 9 r s=7p+8q+9r , find the value of s


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Raymond Chan
Nov 25, 2017

a 2 ( a b ) ( a c ) ( a + x ) + b 2 ( b c ) ( b a ) ( b + x ) + c 2 ( c a ) ( c b ) ( c + x ) p + q x + r x 2 ( a + x ) ( b + x ) ( c + x ) \frac { { a }^{ 2 } }{ \left( a-b \right) \left( a-c \right) \left( a+x \right) } +\frac { { b }^{ 2 } }{ \left( b-c \right) \left( b-a \right) \left( b+x \right) } +\frac { { c }^{ 2 } }{ \left( c-a \right) \left( c-b \right) \left( c+x \right) } \equiv \frac { p+qx+r{ x }^{ 2 } }{ \left( a+x \right) \left( b+x \right) \left( c+x \right) }

Multiply both sides by ( a + x ) ( b + x ) ( c + x ) \left( a+x \right) \left( b+x \right) \left( c+x \right) :

a 2 ( a + x ) ( b + x ) ( c + x ) ( a b ) ( a c ) ( a + x ) + b ( a + x ) ( b + x ) ( c + x ) ( b c ) ( b a ) ( b + x ) + c 2 ( a + x ) ( b + x ) ( c + x ) ( c a ) ( c b ) ( c + x ) p + q x + r x 2 \frac { { a }^{ 2 }\left( a+x \right) \left( b+x \right) \left( c+x \right) }{ \left( a-b \right) \left( a-c \right) \left( a+x \right) } +\frac { { b }\left( a+x \right) \left( b+x \right) \left( c+x \right) }{ \left( b-c \right) \left( b-a \right) \left( b+x \right) } +\frac { { c }^{ 2 }\left( a+x \right) \left( b+x \right) \left( c+x \right) }{ \left( c-a \right) \left( c-b \right) \left( c+x \right) } \equiv p+qx+r{ x }^{ 2 }

Simplify, we have:

a 2 ( b + x ) ( c + x ) ( a b ) ( a c ) + b ( a + x ) ( c + x ) ( b c ) ( b a ) + c 2 ( a + x ) ( b + x ) ( c a ) ( c b ) p + q x + r x 2 \frac { { a }^{ 2 }\left( b+x \right) \left( c+x \right) }{ \left( a-b \right) \left( a-c \right) } +\frac { { b }\left( a+x \right) \left( c+x \right) }{ \left( b-c \right) \left( b-a \right) } +\frac { { c }^{ 2 }\left( a+x \right) \left( b+x \right) }{ \left( c-a \right) \left( c-b \right) } \equiv p+qx+r{ x }^{ 2 }

Put x = a x=-a : a 2 ( b a ) ( c a ) ( a b ) ( a c ) = p + q ( a ) + r ( a ) 2 \frac { { a }^{ 2 }\left( b-a \right) \left( c-a \right) }{ \left( a-b \right) \left( a-c \right) } =p+q\left( -a \right) +r{ \left( -a \right) }^{ 2 }

Simplify, we have:

r a 2 q a + p = a 2 r{ a }^{ 2 }-qa+p={ a }^{ 2 }

Similarly, by putting x = b x=-b and x = c x=-c , we can obtain the following two equations: r b 2 q b + p = b 2 r{ b }^{ 2 }-qb+p={ b }^{ 2 } r c 2 q c + p = c 2 r{ c }^{ 2 }-qc+p={ c }^{ 2 }

Rearrange the three equations, we have: ( r 1 ) a 2 q a + p = 0 \left( r-1 \right) { a }^{ 2 }-qa+p=0 ( r 1 ) b 2 q b + p = 0 \left( r-1 \right) { b }^{ 2 }-qb+p=0 ( r 1 ) c 2 q c + p = 0 \left( r-1 \right) { c }^{ 2 }-qc+p=0

Note that the three equations we obtained share the same format ( r 1 ) y 2 q y + p = 0 \left( r-1 \right) { y }^{ 2 }-qy+p=0

Therefore, we can conclude that the equation ( r 1 ) y 2 q y + p = 0 \left( r-1 \right) { y }^{ 2 }-qy+p=0 has roots a a , b b and c c

However, a a , b b and c c are 3 distinct real constants, so it means the quadratic equation above has 3 distinct roots, which is impossible.

On the other hand, we know that the equation 0 y 2 0 y + 0 = 0 0{ y }^{ 2 }-0y+0=0 can has infinite many solutions.

Therefore, r 1 = 0 r-1=0 , q = 0 q=0 and p = 0 p=0

Finally, we get r = 1 r=1 , q = 0 q=0 and p = 0 p=0

Thus, s = 7 p + 8 q + 9 r = 7 ( 0 ) + 8 ( 0 ) + 9 ( 1 ) = 9 s=7p+8q+9r=7(0)+8(0)+9(1)=\boxed9

A much faster way to solve this question is via cover up rule .

Pi Han Goh - 3 years, 6 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...